Exploring hydrogen storage options: A brief review of gaseous, liquid, and solid-state approaches - Sakinah Hisham; Norazlianie Sazali; Mohd Kamal bin Kamarulzaman (Engineering, Technology & Applied Science Research, 2024)
Hydrogen is a major facilitator of the clean energy transition as the globe shifts to renewable energy utilization. Being an environmentally benign fuel, hydrogen exhibits great potential due to its clean burning into water and high gravimetric energy density. However, achieving the goal of a hydrogen economy is still hampered by ineffective storage technology. The most recent research on hydrogen storage, including gaseous, liquid, and solid-state material storage modalities, is examined in this study. Cryogenic liquefaction provides density even though it wastes energy whereas underground storage provides seasonal capacity but battles leakage. Reversible solid-state materials with favorable kinetics and shielding, such as metal hydrides, are particularly attractive, notwithstanding their capacity limitations. Substantial scientific discoveries are interspersed throughout the performed assessment, ranging from materials that absorb hydrogen 900 times their volume to the excavation of salt caverns in Romania. The present paper also explains how storage requirements for fixed and mobile applications differ significantly. Whether a person is a scientist, an engineer, or a policy maker, this review aims to pique the interest of anybody who wishes to comprehend the limitless potential of hydrogen by providing a thorough yet easily readable overview of the state-of-the-art storage technology, along with opportunities and obstacles.